EFA and Beyond : Service Provision and Quality Assurance in China - Wang, Yidan (World Bank, Washington, DC, 2012)
China is not often thought of in the Education-for-all (EFA) context but its education sector over the past 20 years provides many lessons for countries that are approaching Universal Primary Education (UPE). The most important lesson may be that the need for educational reform does not diminish as countries approach UPE. The first challenge is to expand education opportunities. As coverage expands, however, new challenges inevitably emerge that require constant attention and frequent updates to education policy and financing mechanisms.